Extragradient Method for Fixed Points in CAT(0) Spaces - Yu-Pei Lv; Khurram Shabbir; Sundus Shahzeen; Farman Ali; Jeevan Kafle (Journal of Function Spaces)
This paper is dedicated to construct a viscosity extragradient algorithm for finding fixed points in a CAT(0) space. The mappings we consider are nonexpansive. Strong convergence of the algorithm is obtained. The results established in this work extend and improve some recent discovers in the literature.